Paradox Subjects in A. Mustofa Bisri's Collection of Poems - Suyatno Suyatno; Haris Supratno; Andi Karman (Jurnal Sinestesia, 2023)
This study entitled Paradox Subjects in A. Mustofa Bisri's Collection of Poems. The problem analyzed is the description of paradoxical subjects in A. Mustofa Bisri's collection of poems. This study aims to find meaning in the subject of paradox. The method used is objective hermeneutic method. The data source for this research is a collection of poems by A. Mustofa Bisri, namely Ohoi, Pahlawan dan Tikus dan Negeri Daging. The results of this study indicate that A. Mustofa Bisri's collection of poems can be said to be a paradoxical subject not only presented through diction or not. Paradoxical subjects can also be seen through opposite relations even without having to directly use the antonym form. Like the difference in each line, the paradox is through the difference in epistemology between aqli and naqli through the view that this night is day and this day is night.